Digital finance and metaverse in banking : decoding a virtual reality towards financial inclusion and sustainable development - Kandpal, Vinay; Ozili, Peterson K.; Jeyanthi, P. Mary (Emerald Publishing Limited, 2025)
Digital Finance and Metaverse in Banking explores how emerging technologies can revolutionize banking services, enhance financial inclusion, and contribute to sustainable development goals. With contributions from a range of experts, coverage includes the evolution of digital finance, the integration of metaverse technologies in banking, and the impact on customer experience and accessibility. It also addresses the regulatory, security, and ethical implications of this digital shift. With case studies, expert insights, future predictions, and a comprehensive view of how digital innovations could reshape the landscape of banking and finance, this is an invaluable resource for professionals, policymakers, and enthusiasts in the field.
Includes index.
Keywords: Fintech.; Business & Economics -- Finance -- General.; Financial technology (fintech); Finance and the finance industry.; elektronické knihy; electronic books